Development of BIPA Teaching Materials Based on Cross-Cultural Business Communication Using a Contextual Approach - Isro'iyah, Latifatul; Ima Herminingsih, Dwi (International Journal of Social Science, Education, Communication and Economics, 2024)
The general aim of this research is the Development of BIPA Teaching Materials Based on Cross-Cultural Business Communication Using a Contextual Approach.This study used descriptive qualitative method. Descriptive research is research that describes the situations and events that occur. The research method uses literature study. Literature study is a research method in the form of searching for books, journal articles, literature, notes, reports and literary works related to the problem topic. The data analysis technique used in this research is qualitative data analysis. The research results of the communicative-contextual approach can be applied in BIPA learning. This can be realized in BIPA learning by paying attention to the five principles of the communicative-contextual approach, namely [1] communicative interaction, [2] authentic texts, [3] language learning and learning management, [4] personal experience, and [5] language relationships in the classroom and outside the classroom. The problem of the availability of teaching materials is an issue that continues to grow from year to year. This stems from the fact that existing teaching materials cannot be accessed easily and that existing teaching materials do not meet the needs of teachers and learners, especially in terms of intercultural competence. Therefore, this research develops culture-based teaching materials using a contextual-communicative approach.